Metal-Ligand Stability Constant of Eu(III), Sm(III), Tb(III), Nd(III) and Pr(III) Metal Ion Complex with Some Substituted Isoxazolines - Narwade, M.L. (Asian Journal of Chemistry, 2010)
The interactions of Eu(III), Sm(III), Th(lll), Nd(III) and Pr(III) metal ions with 3-(2-hydroxy-3-bromo-5-methyl-phenyl) 5-(3,4-dioxy methylene) isoxazoline (Ligand No. 1), 3-(2-hydoxy-5-methyl phenyl)-5- (4 methoxyphenyl) isoxazoline (Ligand No 2) and 3-(2-hydroxy-3-bromo- 5-methyl phenyl)-5-(4-methoxyphenyl) isoxazoline (Ligand No.3) have been studied at 0.1M ionic strength. It is observed that lanthanide ions form 1 : 1 and 1 : 2 complexes with all the isoxazoline ligands. The data obtained of pK and log K are used (i) to see the effect of substituents, and (ii) to check the validity of log K = a pK + b.